Analysis of boundary layer nanofluid flow over a stretching permeable wedge-shaped surface with magnetic effect - Ali, M.; Nasrin, R.; Alim, M. A. (Journal of Naval Architecture and Marine Engineering, 2021)
The problem of steady two-dimensional boundary layer flow of momentum, heat and mass transfer over a stretching permeable wedge-shaped surface in a nanofluid in presence of magnetic field has been studied. In this respect, the governing partial differential equations have been converted into ordinary differential equations by using the local similarity transformation. The transformed governing equations have been then solved numerically using the bvp4c in MATLAB software. The effects of the pertinent parameters, namely wedge angle parameter (β), Brownian motion (Nb), thermophoresis (Nt), magnetic parameter (M), moving wedge parameter (λ), permeability parameter (K*), Prandtl number (Pr), and Lewis number (Le) on fluid velocity, thermal and concentration within the boundary layer have been analyzed. The numerical results obtained of the skin friction coefficients, local Nusselt number and local Sherwood number, as well as the velocity, temperature and concentration profiles have been presented graphically and also in tabular form. The results indicate that the momentum boundary layer thickness increases with increasing values of wedge angle and moving wedge but reduces for magnetic and permeability effects. The heat transfer rate increases for wedge angle, moving wedge, Brownian motion but decreases for thermoporesis and magnetic effects. The mass transfer rate decreases for Brownian motion and thermoporesis effects but increases for wedge angle and moving wedge parameters. Finally, the numerical results have been compared with previously published research and found to be in good agreement.